Numerical Simulation of Internal Flow in Screw-Conveyor Atomizer from a Spraying Dust Suppression Device - Ayala, Eduardo (2024)
This article presents a proposition to delve into the intricate internal flow dynamics of a screw-conveyor pressure-swirl atomizer. The objective of the study is to use a comprehensive mathematical model, which will serve as a tool for determining the core dimensions of the atomizer. To verify the accuracy and reliability of the model, rigorous numerical simulations will be conducted. The computational tools employed for the following purpose encompass the utilization of Ansys ICEM CFD software for the creation of a meticulously crafted three-dimensional hexahedral mesh. Subsequently, the Ansys Fluent CFD software is going to be harnessed to execute the simulation of the atomizer’s internal flow behavior. By undertaking the comprehensive analysis, the article aims to shed light on the various merits and demerits inherent in the utilization of such atomizers, particularly concerning their impact on fuel consumption and the intricate sizing aspects. These facets hold paramount significance in the broader realm of mechanical design, specifically in the context of devising efficient dust suppression devices. The numerical simulation of the internal flow is going to be executed employing the RNG k-ε turbulence model, a robust choice to capture the complexities of turbulence. Furthermore, the VOF multiphase model is going to be employed to accurately determine the interface location between the air and liquid phases, enhancing the fidelity of the simulations. In essence, the study strives to provide a comprehensive understanding of the internal flow dynamics of screw-conveyor pressure-swirl atomizers through a combination of advanced mathematical modeling and precise numerical simulations.